"BLUE AND ECONOMY POLICY" AND THEIR IMPACT TO INDONESIAN COMMUNITY WELFARE - Siti Nurhayati (Jurnal Ekonomi Dan Bisnis, 2015)
The main goals of Indonesia development policy is an Indonesian community welfare throught somestrategies that applicated at all development fields. Recently, blue economy concept was developed besidegreen economy. It concepts build after Rio+20 meeting at June 2012 ago in Rio de Janeiro, Brazil. Those meetinghas result a document that call the future we need with stressing on green economy.  Susilo Bambang Yudhoyono, the president of Indonesia talk about his speach moving towardssustainability: together we must create the future we want. So far, United Nations Environment Programe(UNEP) take a theme Green Economy : Does it Include You ?  at World Eviroet Day ereoy, Jue      ,2012. The Blue and Green Economy (BGE) comes as an exact and sustainable solution for environment maintainand focused on three factors : ecology, cocial, and economy. In Indonesia, the BGE applicate together for development policy, that have much impact to economicactivities as a multiplier effect. The more economic activities done, the more income receipt by communities. It isa characteristic of welfare. So, by implement the BGE concept to Indonesian development policy, the impact ofcommunity welfare was realized.Key words : blue and green economy (BGE), community welfare, Rio+20 meeting